2018
DOI: 10.1111/trf.15057
|View full text |Cite
|
Sign up to set email alerts
|

Recent and occult hepatitis B virus infections among blood donors in the United States

Abstract: BACKGROUND: Characteristics of US blood donors with recent (RBI) or occult (OBI) hepatitis B virus (HBV) infection are not well defined. METHODS: Donors with RBI and OBI were identified by nucleic acid and serologic testing among 34.4 million donations during 2009-2015. Consenting donors were interviewed and their HBV S-gene sequenced. RESULTS:The overall rate of HBV-infected donors was 7.95 per 100,000; of these, 0.35 per 100,000 and 1.70 per 100,000 were RBI and OBI, respectively. RBI (n = 120) and OBI (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
5
17
0
Order By: Relevance
“…HBV subgenotype A2 was predominant in all donors (83% in recent infections vs 60% in OBI) versus non‐A2 subtypes (17 and 40%, respectively) with overall more molecular diversity observed in sequences from OBI donors including 50% having 1 or more immune‐escape mutations identified. We conclude that additional surveillance using sensitive NAT methods is needed to measure trends over time .…”
Section: United Statesmentioning
confidence: 96%
See 3 more Smart Citations
“…HBV subgenotype A2 was predominant in all donors (83% in recent infections vs 60% in OBI) versus non‐A2 subtypes (17 and 40%, respectively) with overall more molecular diversity observed in sequences from OBI donors including 50% having 1 or more immune‐escape mutations identified. We conclude that additional surveillance using sensitive NAT methods is needed to measure trends over time .…”
Section: United Statesmentioning
confidence: 96%
“…Finally, in another recent study, the rates, demographics, risk factors for infection and molecular characteristics of recently HBV‐infected Red Cross donors were compared to those with OBI . In this study, recently infected donors were defined as those lacking anti‐HBc but confirmed for HBV DNA with or without HBsAg‐confirmed positivity.…”
Section: United Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…3 In the United States, these two groups represent 26% of the overall rate of 8 per 100,000 HBV donors. 4 Similar figures are not well known in Europe, but certainly the large migration flows from HBV endemic regions in recent times could have changed the former scenario.…”
Section: Discussionmentioning
confidence: 82%